Antique Batik - Dedi Setiawan; Albertus Eka; Denis Mahendra (Journal of the Community Development in Asia (JCDA), 2018)
This analysis paper aims to analyze the readiness of a company to export, analyze analysis of marketing, segmenting, targeting, positioning, and analysis. the company analyzed is a small medium batik industrial company called Antique batik. the batik industry in Indonesia is increasingly developing to penetrate the international market. the development of batik, especially batik, has created a lot of competition in making designs or motifs from batik. In the midst of increasingly competitive competition the determination of copyright is a necessity for businesses. the analytical method used is by conducting direct interviews to find out the strengths and threats from external parties. The results of the interview revealed that there was a threat from outside parties which was a duplication and modification of the copyright of batik motifs from Antique batik products. analysis continues to analyze the ways in which products can be promoted to potential markets abroad by using social media effectively. The results of the analysis from the study explained that Antique batik had physically exported batik well, as evidenced by regular exhibition participation and always getting orders from other countries. then to help optimize sales, it is necessary to do marketing on social media or websites and normalize copyright for the purpose of avoiding plagiarism and extracting Indonesian culture into the world. The conclusion is that Antique Batik companies need to do marketing on social media or websites to get more exposure from the public so that the company's brand image can be built and to cover the company's threat to copying the right to protect copying and extract Indonesian culture into the world.